Measuring Self-Reported Well-Being of Physicians Using the Well-Being Thermometer: Cohort Study - Marios Adamou; Sarah L Jones; Niki Kyriakidou; Andrew Mooney; Shriti Pattani; Matthew Roycroft (JMIR Formative Research)
Abstract BackgroundAdvancements in medical science have focused largely on patient care, often overlooking the well-being of health care professionals (HCPs). This oversight has consequences; not only are HCPs prone to mental and physical health challenges, but the quality of patient care may also endure as a result. Such concerns are also exacerbated by unprecedented crises like the COVID-19 pandemic. Compared to other sectors, HCPs report high incidence of stress, depression, and suicide, among other challenging factors that have a significant negative impact on their well-being. ObjectiveGiven these substantial concerns, the development of a tool specifically designed to be used in clinical settings to measure the well-being of HCPs is essential. MethodsA United Kingdom–based cross-sectional pilot study was carried out to measure self-reported well-being in a cohort of 148 physicians, using the newly developed well-being thermometer. The aim of the tool is to allow respondents to develop an individual sense of “well-being intelligence” thus supporting HCPs to have better insight and control over their well-being and allow insights into how to manage it. The tool consists of 5 well-being domains—health, thoughts, emotions, spiritual, and social. Each domain can be measured individually or combined to produce an overall well-being score. ResultsThe tool demonstrated good internal consistency; the Cronbach α in this study was 0.84 for the total scale. ConclusionsResults from this cohort demonstrated that the well-being thermometer can be used to gather intelligence of staff well-being. This is a promising new tool that will assist HCPs to recognize their own well-being needs and allow health care organizations to facilitate change in policies and practices to reflect a better understanding of staff well-being.